2016
DOI: 10.1007/s40808-016-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-GCM ensembles performance for climate projection on a GIS platform

Abstract: Climate impact studies especially in the field of hydrology often depend on climate change projections at fine spatial resolution. General circulation models (GCMs), which are the tools for estimating future climate scenarios, run on a very coarse scale, so the output from GCMs need to be downscaled to obtain a finer spatial resolution. This paper aims to present GIS platform as a downscaling environment through a suggested algorithm, which applies statistical downscaling models to multidimensional GCMEnsemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…A full review of how that field is developing is beyond the scope of this paper, but it is worth noting that recognition of structural uncertainty (i.e., uncertainty pertaining to the model assumptions, formulation, and internal connections) has been a key part of these modeling efforts. The use of Bayesian approaches and model ensembles to provide ranges of possible outcomes across model types is now becoming more common (e.g., Gharbia et al, 2016). The first use of model ensembles was in economics (Bates and Granger, 1969) but has now become a staple of many fieldseconomics, systematics, meteorology, and climatology-and is often now used when considering shifting species distributions (e.g., Ara煤jo and New, 2007) or terrestrial ecosystem impacts (Baker et al, 2019).…”
Section: Handling Uncertaintymentioning
confidence: 99%
“…A full review of how that field is developing is beyond the scope of this paper, but it is worth noting that recognition of structural uncertainty (i.e., uncertainty pertaining to the model assumptions, formulation, and internal connections) has been a key part of these modeling efforts. The use of Bayesian approaches and model ensembles to provide ranges of possible outcomes across model types is now becoming more common (e.g., Gharbia et al, 2016). The first use of model ensembles was in economics (Bates and Granger, 1969) but has now become a staple of many fieldseconomics, systematics, meteorology, and climatology-and is often now used when considering shifting species distributions (e.g., Ara煤jo and New, 2007) or terrestrial ecosystem impacts (Baker et al, 2019).…”
Section: Handling Uncertaintymentioning
confidence: 99%
“…As suggested by Weigel et al [78] and Hagedorn et al [79], the multimodel ensemble improves reliability and reduces the uncertainty of climate projections and forecasting. For hydrological research, Gharbia et al [80] suggested utilizing the multimodel ensemble for climate change simulations and confirmed that it can be directly used in the hydrological models. A study by Yokohata et al [81] concluded that the CMIP3 ensemble is reasonably reliable on large scales.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that location plays a central role in integrating information about the society, the economy, and the environment [13,14]. In addition, cross-border challenges such as climate change, disasters, peace and security, and quality of the environment can only be solved through coordinated global and regional efforts [2,15,16]. In recognition of the power geographical locations and geospatial information play in development planning, the United Nations Statistical Commission endorsed a work program in 2013 to develop a statistical spatial framework that would become an international standard for the integration of statistical and geospatial information [17].…”
Section: Introductionmentioning
confidence: 99%